Quiescent-Interval Slice Selective Magnetic Resonance Angiography for Abdominal Aortic Aneurysm Treatment Planning. (June 2021) - Kazemtash, Majid; Harth, Marc; Derwich, Wojciech; Thalhammer, Axel; Schmitz-Rixen, Thomas; Keese, Michael
Purpose: Diagnostic imaging of Abdominal aortic aneurysm (AAA) almost exclusively employs CT angiography (CTA) involving X-ray exposure and contrast medium that may harm some patients. Quiescent-Interval Slice Selective MR (QISS-MR) depicts vascular anatomy without radiation or contrast medium. The diagnostic quality of QISS-MRA and CTA were compared in regard to length and diameter measurements in AAA patients. Suitability of QISS-MRA for AAA treatment planning was evaluated. Materials and Methods: The details of 30 patients with AAA who received both a QISS-MR and CTA for a known infrarenal AAA were obtained retrospectively that was approved by the local research ethics board. Two observers analyzed each dataset in terms of image quality and determined lumen diameter and length of 15 vessel segments. Results: Highly accurate agreement between the diagnostic scores from the two observers was achieved. There was no significant difference between CTA and QISS-MRA for all 15 measured vessels. Although information on calcification was lacking and intraluminal thrombus was visualized in only 25 patients out of 30 patients, a founded decision to carry out OR or EVAR was possible with both imaging modalities. Conclusion: QISS-MRA presents a radiation and contrast free method for preoperative diagnostic AAA imaging. While QISS-MRA does not deliver exact information regarding calcification and thrombus formation, it does accurately allow measurement of vessel diameter and length. Therefore, it is potentially useful for EVAR planning in selected patients with impaired renal function.